A three-dimensional macroporous antimony@carbon composite as a high-performance anode material for potassium-ion batteries. Issue 16 (3rd April 2019) - He, Xiao-Dong; Liu, Ze-Hua; Liao, Jia-Ying; Ding, Xiang; Hu, Qiao; Xiao, Li-Na; Wang, Shuo; Chen, Chun-Hua
Abstract : A novel three-dimensional macroporous antimony@carbon composite is fabricated by a simple KCl template method with a single bi-functional precursor potassium antimony tartrate. Abstract : Potassium-ion batteries (KIBs) are considered important substitutes for lithium-ion batteries (LIBs) owing to the abundance of K resources. Herein, a novel three-dimensional macroporous antimony@carbon composite (Sb@C-3DP) is fabricated by a simple KCl template method with a single bi-functional precursor potassium antimony tartrate. The Sb@C-3DP electrode delivers an excellent rate capability (286 mA h g −1 at 1 A g −1 ) and remarkable reversible capacity (516 mA h g −1 at a low current density of 0.05 A g −1 ). Moreover, an outstanding long-term cycling stability (97% capacity retention after 260 cycles) is also achieved, which is benefited from the unique microstructure that can accommodate the huge volumetric change of Sb during depotassiation and potassiation processes. A full cell constructed by coupling Sb@C-3DP with a Prussian blue cathode exhibits a high energy density (197.6 W h kg −1 ) and power density (2067.9 W kg −1 ).